2019
DOI: 10.1038/s41586-019-1842-7
|View full text |Cite
|
Sign up to set email alerts
|

Impaired cell fate through gain-of-function mutations in a chromatin reader

Abstract: Modifications of histone proteins have essential roles in normal development and human disease. Recognition of modified histones by 'reader' proteins is a key mechanism that mediates the function of histone modifications, but how the dysregulation of these readers might contribute to disease remains poorly understood. We previously identified the ENL protein as a reader of histone acetylation via its YEATS domain, linking it to the expression of cancer-driving genes in acute leukaemia 1 . Recurrent hotspot mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
118
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(149 citation statements)
references
References 20 publications
6
118
0
1
Order By: Relevance
“…Importantly, targeting this H3K4me3-specific reader could also be beneficial for coinciding blocking of all three oncogenic proteins. Histone readers are increasingly considered to be druggable, and a number of potent inhibitors of acetyllysine recognizing bromodomain and YEATS domain have been developed in the past 10 years [24][25][26][27] . The pioneering studies 8,9,22 uncovering the pivotal role of the histone binding by the PHD finger of KDM5A, PHF23, and BPTF in NUP98 fusions in leukemic transformation and the feasibility of targeting these fusions by small molecules together with our mechanistic findings further suggest that impairing the PHD finger function and/or structure may provide an effective way to treat AMLs associated with these NUP98 fusions.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, targeting this H3K4me3-specific reader could also be beneficial for coinciding blocking of all three oncogenic proteins. Histone readers are increasingly considered to be druggable, and a number of potent inhibitors of acetyllysine recognizing bromodomain and YEATS domain have been developed in the past 10 years [24][25][26][27] . The pioneering studies 8,9,22 uncovering the pivotal role of the histone binding by the PHD finger of KDM5A, PHF23, and BPTF in NUP98 fusions in leukemic transformation and the feasibility of targeting these fusions by small molecules together with our mechanistic findings further suggest that impairing the PHD finger function and/or structure may provide an effective way to treat AMLs associated with these NUP98 fusions.…”
Section: Resultsmentioning
confidence: 99%
“…6e ). A recent study reported that oncogenic mutations of ENL identified in Wilms tumor drove aberrant gene transcription by enhancing self-association ability of ENL, and the self-association ability of ENL mutants relied on the IDR region and the ET (also called AHD) domain of ENL 32 . Thus, it is a general feature for YET-family proteins to form the central hub to concentrate many complexes to a compartmentalized unit for efficient transcription, reinforcing the notion that YET-family proteins are master transcriptional regulators in cells 3 , 14 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent hot spot mutations have been found in ENL YEATS domain in WTs [ 208 ]. ENL protein is a reader of histone acetylation through its YEATS domain.…”
Section: Wilms Nephroblastomamentioning
confidence: 99%
“…ENL protein is a reader of histone acetylation through its YEATS domain. Using human and mouse cellular models, evidence was provided that ENL mutants induce gene expression changes that promote a premalignant condition and in nephrogenesis models induce the formation of undifferentiated cellular structures resembling those observed in WTs [ 208 ]. At mechanistic level, these ENL mutations exhibit a function similar to their normal counterpart, occupying similar target genomic loci, but with a clearly increased occupancy, leading to a pronounced increase in the recruitment and activity of transcription elongation machinery, thus enforcing the rate and the level of gene transcription of these target genes [ 208 ].…”
Section: Wilms Nephroblastomamentioning
confidence: 99%